Assessing academics’ knowledge sharing intention in institutions of higher learning - Fauri @ Fauzi, Muhammad Ashraf (2016)
Knowledge sharing (KS) in Institutions of Higher Learning (IHL) is a noble culture and should be fostered.IHL is the best platform for knowledge to be disseminated among academics and students. This research adapts the Theory of Planned Behavior (TPB) to determine academics’ KS intention in Malaysian IHL.Partial least square SEM is used for analysis.Respondents consist of 45 academics acquired from 399 surveys.Results show that only social network is a significant factor in academics’ attitude towards KS intention, while commitment and trust are not.Management support, social media towards subjective norm, and PBC are significant factors for KS intention.Subsequently, attitude and PBC are significant determinants of intention to share and subjective norm is not significant.The findings of this study enable IHL’s management to identify the factors to focus on when addressing the issues pertaining to hiring academics.